Task cues lead to item-level backward inhibition with univalent stimuli and responses. Issue 3 (March 2020) - Prosser, Laura J; Jackson, Margaret C; Swainson, Rachel
Backward inhibition may aid our ability to switch between tasks by counteracting the tendency to repeat a recently performed task. Current theory asserts that conflict between tasks during performance plays a key role in inducing the effect. However, a study by Costa and Friedrich suggests that backward inhibition might occur without this type of conflict being present. To better understand the mechanisms underlying backward inhibition, we investigated the roles of between-task conflict, task-based instructions, and task cues. Experiment 1 tentatively supported the view that conflict between tasks is not necessary for backward inhibition to be present, and suggested that either the use of task-based instructions or the provision of specific task cues might be sufficient to generate the effect. Experiment 2 ruled out task-based instruction as a likely cause of backward inhibition in this context. Experiment 3 showed that the provision of task cues was sufficient to drive a significant backward inhibition effect, but only when stimuli and responses (as well as tasks) repeated. Overall, these results indicate that between-task conflict during performance is not necessary for backward inhibition to be applied, and that task cues have a key role in generating the effect.